2024
DOI: 10.1111/ppa.13854
|View full text |Cite
|
Sign up to set email alerts
|

Levan differentially primes barley defence against infections by Fusarium graminearum, Rhizoctonia solani and Pyricularia oryzae

Dan Lian,
Chen Shui,
Ling Yang
et al.

Abstract: The widespread use of pesticides poses significant challenges to the safety of agricultural products and the ecological environment. Levan‐type fructans have the ability to act as an induced resistance stimulus, enhancing plant disease resistance, which aligns with the principles of green development. This study showed that levan polysaccharide, produced by Halomonas smyrnnensis levansucrase, could induce the resistance of barley to Fusarium graminearum much better than inulin‐type fructans or low‐molecular‐we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Levan and LOS do not cause immediate defense responses (ROS burst) upon application, preventing temporal growth retardation effects (Janse . Data presented here and elsewhere (Lian et al, 2024) reduced B. cinerea disease symptoms on tomato leaves by 25% when applied to the roots (Cawoy et al, 2014) and by 50% on bean leaves when applied to the leaves (Samares et al, 2021a). Foliage treatment with 12.5 g L À1 COS-OGA, a sugar complex of chitooligosaccharides associated with oligogalacturonides (commercially available as Fytosave), resulted in an average 50% reduction in powdery mildew disease symptoms on tomato leaves, depending on the powdery mildew inoculum present in the greenhouse at the start of the experiment (van Aubel et al, 2016).…”
Section: Tomato Seed Defense Priming Againstmentioning
confidence: 56%
See 1 more Smart Citation
“…Levan and LOS do not cause immediate defense responses (ROS burst) upon application, preventing temporal growth retardation effects (Janse . Data presented here and elsewhere (Lian et al, 2024) reduced B. cinerea disease symptoms on tomato leaves by 25% when applied to the roots (Cawoy et al, 2014) and by 50% on bean leaves when applied to the leaves (Samares et al, 2021a). Foliage treatment with 12.5 g L À1 COS-OGA, a sugar complex of chitooligosaccharides associated with oligogalacturonides (commercially available as Fytosave), resulted in an average 50% reduction in powdery mildew disease symptoms on tomato leaves, depending on the powdery mildew inoculum present in the greenhouse at the start of the experiment (van Aubel et al, 2016).…”
Section: Tomato Seed Defense Priming Againstmentioning
confidence: 56%
“…More research is required on a wider array of monocot species to conclude whether monocots may be less receptive to treatments with fructans, fructan-metabolizing bacteria and their combinations. However, it was recently demonstrated that levan from Halomonas smyrnensis could generate biological effects on barley, protecting the plants against several diseases (Lian et al, 2024),…”
Section: Tomato Seed Defense Priming Againstmentioning
confidence: 99%